Guardians of the Land: Essays on Central African Territorial Cults - Schoffeleers, J. M. (Mambo Press, 1979)
Though Malawi and Central Africa are now predominantly Christian countries, African tradition relgion remains important everywhere. Now a classic, this study was first published in 1979 against the background of neglect in publishing texts on economic and social history and other aspects of cultural development. It provides important information on Central African territorial cults, and it one of a series recording the history of African religious systems. Ten scholars report on detailed case studies conducted in Zambia, Malawi and Zimbabwe.
Keywords: Religion / Indigenous; Folk & Tribal